Atomic‐Scale Valence State Distribution inside Ultrafine CeO2 Nanocubes and Its Size Dependence. Issue 42 (9th September 2018) - Hao, Xiaodong; Yoko, Akira; Chen, Chunlin; Inoue, Kazutoshi; Saito, Mitsuhiro; Seong, Gimyeong; Takami, Seiichi; Adschiri, Tadafumi; Ikuhara, Yuichi
Abstract: Atomic‐scale analysis of the cation valence state distribution will help to understand intrinsic features of oxygen vacancies ( V O ) inside metal oxide nanocrystals, which, however, remains a great challenge. In this work, the distribution of cerium valence states across the ultrafine CeO2 nanocubes (NCs) perpendicular to the {100} exposed facet is investigated layer‐by‐layer using state‐of‐the‐art scanning transmission electron microscopy‐electron energy loss spectroscopy. The effect of size on the distribution of Ce valence states inside CeO2 NCs is demonstrated as the size changed from 11.8 to 5.4 nm, showing that a large number of Ce 3+ cations exist not only in the surface layers, but also in the center layers of smaller CeO2 NCs, which is in contrast to those in larger NCs. Combining with the atomic‐scale analysis of the local structure inside the CeO2 NCs and theoretical calculation on the V O forming energy, the mechanism of size effect on the Ce valence states distribution and lattice expansion are elaborated: nano‐size effect induces the overall lattice expansion as the size decreased to ≈5 nm; the expanded lattice facilitates the formation of V O due to the lower formation energy required for the smaller size, which, in principle, provides a fundamental understanding of the formation and distribution of Ce 3+ inside ultrafine CeO2 NCs. Abstract : Atomic‐scale cerium valence state distribution layer‐by‐layer in the surfactant‐modified CeO2 nanocubes is achieved using scanning transmission electron microscopy and electron energy loss spectroscopy. It is demonstrated that the increasing amount of Ce 3+ in the center layers of CeO2 nanocube (as the size reduced to approximately 5 nm) is related to the nanosize‐effect induced local lattice expansion.